Bimtek Pemanfaatan Smart Feeding Fish Automatic Berbasis Internet of Things untuk Efisiensi Budi Daya Perikanan di Desa Sukajadi, Bogor - Devi Puspita Sari; Waskita Cahya; Benecditus Harjo Baskoro; Boy Firmansyah; Astried Silvanie; Ari Kurniawan; Erdhiek Ardianto; Muhammad Febriansyah; Taruna Nasution (Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Consistent and timely fish feeding is a critical factor in supporting optimal fish growth and achieving the expected harvest outcomes. Many small-scale aquaculture practices still operate inefficiently, often resulting in delayed feeding schedules that negatively affect productivity. This community service program aims to provide technical guidance on the utilization of an IoT-based Smart Feeding Fish Automatic system designed to automate fish feeding processes and enable remote monitoring of feed conditions. The system employs a microcontroller integrated with an Android smartphone, allowing users to set feeding schedules and control the device according to specific operational needs. Through this technology, fish farmers in Sukajadi Village, Bogor, are expected to improve the efficiency of their aquaculture management and enhance the quality and quantity of their production.